Charitable Donations by China's Private Enterprises - Björn Anders Gustafsson; Xiuna Yang; Gang Shuge; Dai Jianzhong (Institute for the Study of Labor (IZA), 2016)
The number of private enterprises in China has grown rapidly, and donations from them are an important source of philanthropy in China today. This paper investigates donations given in 2011 by private enterprises using a survey of data covering all 31 provincial-level units of China. The data show that philanthropy practised by Chinese private enterprises is widespread, but the amounts of donations are unequally distributed. Furthermore, donations are positively related to a company's profit and in most cases also to the owner's political participation as expressed in membership in the People's Congress (PC) as well as the Chinese People's Political Consultative Conference (CPPCC) at different levels. Donating is also positively related to the presence of a branch of the Communist Party of China and a trade union within the firm. In contrast, there is little support for donations being related to the characteristics of the major owner in the business, such as their gender, age, previous employment experience, party membership or to the governance structure or location of the private firms.
Keywords: D64; H84; L26; 330; China; philanthropy; donations; private enterprises